Trypanosoma cruzi: Infectivity modulation of a clone after passages through different hosts - Pérez Brandan, Cecilia María (2006)
Although Trypanosoma cruzi virulence can be modified through passages in vivo or long-term in vitro culture, the mechanisms involved are poorly understood. Here we report modifications in the infectivity of a T. cruzi clone after passages in different hosts without detectable changes in parasite genetic patterns. A clone was obtained from a T. cruzi IIe isolate and showed to be less virulent than the original isolate (p < 0.05). This clone was enzymatically similar to the original isolate as shown by multilocus enzyme electrophoresis. Infection of this clone was compared by successive passages in mice and guinea pigs. The mouse-passaged subline became more virulent for both host species compared to the guinea pig-passaged subline (p < 0.05). The clone line displayed similar random amplified polymorphic DNA patterns before and after passages in different hosts suggesting that alterations in virulence could be a result of a differential expression of virulence factors.